2022
DOI: 10.3892/mi.2022.50
|View full text |Cite
|
Sign up to set email alerts
|

Role of pulmonary function testing in inflammatory bowel diseases (Review)

Abstract: Inflammatory bowel disease (IBD) is a term used to describe chronic inflammatory entities of the gastrointestinal system with an unclear etiology. Extra-intestinal manifestations beyond the involvement of the gastrointestinal tract can also occur. Several studies have investigated the alterations of pulmonary function tests (PFTs) in patients with IBD. To the best of our knowledge, the present review article is the first to summarize all the types of PFTs that have been performed in patients with IBD. Contradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Remarkably, only 43% of patients with active IBD had respiratory symptoms, measured with a positive Medical Research Council dyspnea score (five-graded clinical symptom score). Diffusing capacity for carbon monoxide (DLCO)-impaired values are the most common finding in the PFTs of IBD patients [73]. Reduced DLCO values have been described in IBD patients [70,[74][75][76][77][78][79][80][81][82], with some studies associating lung involvement with IBD activity [70,[74][75][76]78,81,82].…”
Section: Subclinical Pulmonary Dysfunction In Ibdmentioning
confidence: 99%
“…Remarkably, only 43% of patients with active IBD had respiratory symptoms, measured with a positive Medical Research Council dyspnea score (five-graded clinical symptom score). Diffusing capacity for carbon monoxide (DLCO)-impaired values are the most common finding in the PFTs of IBD patients [73]. Reduced DLCO values have been described in IBD patients [70,[74][75][76][77][78][79][80][81][82], with some studies associating lung involvement with IBD activity [70,[74][75][76]78,81,82].…”
Section: Subclinical Pulmonary Dysfunction In Ibdmentioning
confidence: 99%
“…These abnormalities may indicate the presence of a subclinical inflammatory state, even in the absence of symptoms. However, evidence regarding the association of pulmonary function tests (PFTs) with disease activity remains controversial [4]. Some reports have indicated that these abnormalities also persist and have been observed during clinical remission of the disease, suggesting a latent subclinical inflammatory reaction [5].…”
Section: Introductionmentioning
confidence: 99%
“…They provide vital information regarding the function of the large and small airways, the lung parenchyma, as well as the size and integrity of the pulmonary capillary bed. Although they do not provide a diagnosis in and of themselves, diverse patterns of anomalies are detected in various respiratory disorders, which aid in diagnosis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%